The impact of regular sperm donation on bulls’ seminal plasma hormonal profile and phantom response - Alicja Kowalczyk (Nature Portfolio, 2021)
Abstract The aim of this study was to analyze the relationship between the concentration of hormones in the seminal plasma, the bull maintenance system in the insemination station, and the regularity of sperm donation and the response to the phantom (libido level). An additional goal was to determine whether there is a relationship between the hormonal profile in the blood, the sperm plasma, the oxidative and antioxidant profile in the blood of bulls and the biometry of their testicles and scrotum, as well as the quality of their sperm in both different seasons and intensities of reproductive use. For the study, 220 healthy and sexually mature Polish Holstein–Friesian bulls were used. They all had normal libido and were fed equally. The animals were grouped according to the scheme: young (16–20 month/n = 60) and old (26–30 month/n = 60) including: individually housed (n = 30) and group housed (n = 30) young, old individually housed (n = 30) and group housed (n = 30) (n total animals = 120); young animals donating semen once a week (every Thursday) (n = 25) and sporadically (once every two months on a random day of the week) (n = 25), old animals donating semen once a week (every Thursday) (n = 25 ) and sporadic donors (once every two months on a random day of the week) (n = 25) (n total animals = 100). When analyzing the results of this study, it should be stated that regular use has a positive effect on the secretion of sex hormones in bulls. Higher levels of testosterone and lower levels of estradiol and prostaglandins resulted in higher sexual performance, expressed by a stronger response to the phantom. The differences in favor of regular use were independent of the bull's age. The results of our research illustrate that the quality of semen and its freezing potential may depend on the season and frequency of its collection, as well as on the age of the males.